Предмет: Алгебра,
автор: kusays
упростите выражение!!!!
Приложения:
Ответы
Автор ответа:
1
Ответ:
(4x² - 5x + 1)(7x² - 2x - 6) = 28x⁴ - 8x³ - 24x² - 35x³ + 10x² + 30x + 7x² - 2x -6 = 28x⁴ - 43x³ - 7x² + 28x - 6
Автор ответа:
0
Ответ:28x^4-43x^3+24x^2-2x-18
Объяснение:
(4x^2-5x+1)(7x^2-2x-6)=28x^4-35x^3+7x^2-8x^3+10x^2-6+7x^2-2x-6=28x^4-43x^3+24x^2-2x-18
Похожие вопросы
Предмет: Русский язык,
автор: Adidas5
Предмет: Русский язык,
автор: Safi
Предмет: Русский язык,
автор: Anti7575
Предмет: Литература,
автор: vadievramzan
Предмет: Алгебра,
автор: Аноним